Senior administrator's selection in India - Maheswari, S.R
Being one of the most advanced governments of the world with a very large bureaucracy, the Government of India still does not have a permanent civil service of its own particularly at the upper and middle levels. Attempts to create a permanent civil service were made since the enforcement of the 1919. Government of India Act until after the independence of India in 1947 as evidenced by the staffing schemes implemented thereafter. Appointments in the higher level are controlled by the Cadre Authority, the Senior Selection Board, the Central Establishment Board, the Establishment Officer and the Appointments Committee of the Cabinet. But no matter how stiff the competition becomes at the top of the administ
Keywords: Selection; India; Civil Service; Civil Service - India